Formation of Hierarchical Co9S8@ZnIn2S4 Heterostructured Cages as an Efficient Photocatalyst for Hydrogen Evolution - Wang, Sibo; Guan, Bu Yuan; Wang, Xiao; Lou, Xiong Wen David (Journal of the American Chemical Society, 2018)
Here we demonstrate the delicate design and construction of hierarchical Co9S8@ZnIn2S4 heterostructured cages as an efficient photocatalyst for hydrogen evolution with visible light. Two photoactive sulfide semiconductors are rationally integrated into a hierarchical hollow structure with strongly coupled heterogeneous shells and two-dimensional ultrathin subunits. The unique architecture can efficiently facilitate the separation and transfer of light-induced charges, offer large surface area, and expose rich active sites for photocatalytic redox reactions. Owing to the distinctive structural and compositional benefits, the hierarchical Co9S8@ZnIn2S4 hollow heterostructures without using any cocatalysts show remarkable activity with a hydrogen-producing rate of 6250 μmol h–1 g–1 and high stability for photocatalytic water splitting.